Anemia induces gut inflammation and injury in an animal model of preterm infants. Issue 4 (21st March 2019) - Arthur, Connie M.; Nalbant, Demet; Feldman, Henry A.; Saeedi, Bejan J.; Matthews, Jason; Robinson, Brian S.; Kamili, Nourine A.; Bennett, Ashley; Cress, Gretchen A.; Sola‐Visner, Martha; Jones, Rheinallt M.; Zimmerman, M. Bridget; et al.
Abstract : BACKGROUND: While very low birth weight (VLBW) infants often require multiple red blood cell transfusions, efforts to minimize transfusion‐associated risks have resulted in more restrictive neonatal transfusion practices. However, whether restrictive transfusion strategies limit transfusions without increasing morbidity and mortality in this population remains unclear. Recent epidemiologic studies suggest that severe anemia may be an important risk factor for the development of necrotizing enterocolitis (NEC). However, the mechanism whereby anemia may lead to NEC remains unknown. STUDY DESIGN AND METHODS: The potential impact of anemia on neonatal inflammation and intestinal barrier disruption, two well‐characterized predisposing features of NEC, was defined by correlation of hemoglobin values to cytokine levels in premature infants and by direct evaluation of intestinal hypoxia, inflammation and gut barrier disruption using a pre‐clinical neonatal murine model of phlebotomy‐induced anemia (PIA). RESULTS: Increasing severity of anemia in the preterm infant correlated with the level of IFN‐gamma, a key pro‐inflammatory cytokine that may predispose an infant to NEC. Gradual induction of PIA in a pre‐clinical model resulted in significant hypoxia throughout the intestinal mucosa, including areas where intestinal macrophages reside. PIA‐induced hypoxia significantly increased macrophage pro‐inflammatory cytokine levels, while reducing tight junction protein ZO‐1 expression and increasing intestinal barrier permeability. Macrophage depletion reversed the impact of anemia on intestinal ZO‐1 expression and barrier function. CONCLUSIONS: Taken together, these results suggest that anemia can increase intestinal inflammation and barrier disruption likely through altered macrophage function, leading to the type of predisposing intestinal injury that may increase the risk for NEC.